2010
DOI: 10.1007/s12265-010-9234-2
|View full text |Cite
|
Sign up to set email alerts
|

Early Increase in Myocardial Perfusion After Stem Cell Therapy in Patients Undergoing Incomplete Coronary Artery Bypass Surgery

Abstract: Incomplete revascularization is associated with worse long-term outcomes. Autologous bone marrow cells (BMC) have recently been tested in patients with severe coronary artery disease. We tested the hypothesis that intramyocardial injection of autologous BMC increases myocardial perfusion in patients undergoing incomplete coronary artery bypass grafting (CABG). Twenty-one patients (19 men), 59 ± 7 years old, with limiting angina and multivessel coronary artery disease (CAD), not amenable to complete CABG were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Ischemic cardiomyopathy (IC) involves changes in the cardiac structure, including thinning of the infarcted wall, cardiac dilatation, remodeling due to apoptosis and necrosis of cardiac myocytes, hypertrophy, fibrosis, and the infiltration of inflammatory cells. 4,5 Cell therapy has shown promising results in several preclinical studies [6][7][8][9][10] and clinical trials [11][12][13][14] that have reported the safety and efficacy of cell transplantation for a wide range of therapeutic applications. Stem/progenitor cellbased therapies have been demonstrated to be effective for tissue engineering and have potential applicability for therapeutic neovascularization, vascular repair, and tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic cardiomyopathy (IC) involves changes in the cardiac structure, including thinning of the infarcted wall, cardiac dilatation, remodeling due to apoptosis and necrosis of cardiac myocytes, hypertrophy, fibrosis, and the infiltration of inflammatory cells. 4,5 Cell therapy has shown promising results in several preclinical studies [6][7][8][9][10] and clinical trials [11][12][13][14] that have reported the safety and efficacy of cell transplantation for a wide range of therapeutic applications. Stem/progenitor cellbased therapies have been demonstrated to be effective for tissue engineering and have potential applicability for therapeutic neovascularization, vascular repair, and tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades our group has worked to developing stem cell-based therapies to treat myocardial infarction building tools [35][36][37][38] and testing trending therapies [9,11,12,39,40] always aiming patients [6][7][8]. Adult stem cell approaches to treat MI have yet to yield relevant results clinically [41] and it is generally accepted that other approaches are needed [42].…”
Section: Independently Of This Limitation Several Groups Demonstratementioning
confidence: 99%
“…Alternatively, stem cell-based therapies have been proposed to overcome the lack of heart re-muscularization within the available therapeutics [5]. Remarkably, multipotent stem cells isolated from adult tissues such as bone marrow [6][7][8][9][10] and adipose tissue [11,12] have demonstrated unsatisfactory heart regeneration performance. Conversely, human pluripotent stem cells such as embryonic stem cells (hESCs) [13] and induced pluripotent stem cells (hiPSCs) [14,15] are promising sources for generating cardiomyocytes (hPSC-CMs) in vitro [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative procedures, such as using laser beams [58], stem cells [59] and even variations in the use of internal thoracic artery [60] have been described, but are part of the treatment of a special group of patients, which is certainly not fit into the daily routine.…”
Section: Coronary Artery Bypass Grafting: Current Considerationsmentioning
confidence: 99%